2014
DOI: 10.1007/s00520-014-2325-x
|View full text |Cite
|
Sign up to set email alerts
|

Professional educational needs for chemotherapy-induced nausea and vomiting (CINV): multinational survey results from 2,388 health care providers

Abstract: Purpose Because as many as 30% of cancer patients who receive chemotherapy of moderate or high emetogenic potential suffer from chemotherapy-induced nausea and vomiting (CINV), we undertook a multinational survey to identify healthcare providers’ perceived knowledge gaps, barriers, and educational interests relevant to CINV. Methods An Internet-based survey was developed and was electronically disseminated to members of Medscape, an international Internet-based continuing medical education provider. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 9 publications
3
47
0
Order By: Relevance
“…We wholeheartedly agree with Tendas et al that education on chemotherapy-induced nausea and vomiting (CINV) in bone marrow transplant (BMT) patients is important and might improve outcomes [1][2][3][4].…”
Section: Dear Editorsupporting
confidence: 76%
See 2 more Smart Citations
“…We wholeheartedly agree with Tendas et al that education on chemotherapy-induced nausea and vomiting (CINV) in bone marrow transplant (BMT) patients is important and might improve outcomes [1][2][3][4].…”
Section: Dear Editorsupporting
confidence: 76%
“…While we did not ask our survey participants if they took care of BMT patients, one could speculate that the 15-22 % who indicated they disagreed with the need for education on this topic were likely not involved with BMT patients [1]. Importantly, in our survey, a full 78 to 85 % of hematology/ oncology physicians and nurses, respectively, indicated they either agreed or strongly agreed that education on the prevention/management of CINV in BMT is warranted.…”
Section: Dear Editormentioning
confidence: 89%
See 1 more Smart Citation
“…Worldwide rates of treatment for delayed CINV, therefore, seem to exhibit substantial variability. Surveys of health care providers have revealed that cost-and patient-related issues are frequently cited as barriers to treating CINV (24,25). In those countries with low rates of prophylactic therapy, these factors should be considered if or when programs are implemented to increase the use of antiemetic medications.…”
Section: Discussionmentioning
confidence: 99%
“…Poorly controlled chemotherapy-induced nausea and vomiting (CINV) negatively affects patient health, quality of life and chemotherapy compliance [1][2][3][4][5][6][7], and is associated with increased resource utilization and healthcare costs [7][8][9][10]. Despite comprehensive antiemetic treatment guidelines [11][12][13][14], there is still an unmet clinical need to improve the prevention of CINV.…”
mentioning
confidence: 99%